Assessment of rainfall variability and its trend over Betul district, Madhya Pradesh - SHARMA, GAURAV; KUMAR, ANKIT; JAIN, SUKANT (Journal of Soil and Water Conservation, 2022)
Most of the natural phenomenons are affected by climate change; the hydrological cycle is one such process which is affected by changes in climate. Therefore, it is important to understand the pattern of rainfall for its management and planning for proper utilization. In the present study, trend assessment was carried out for climate change impact assessment. The non-parametric Mann–Kendall test and Sen’s slope estimator along with different statistical approaches were applied to rainfall data from 1980-2018 (39 years) for Betul district. The average annual rainfall in the region is 1070 mm. The assessment using statistical approach indicates the areal variability of rainfall in the region. The extreme event that is oneday maximum rainfall is also showing an increasing trend. The assessment of rainfall trends indicates that the seasonal and annual rainfall is increasing, but the rate of increase is not statistically significant. It is critically important to assess such changes that are occurred due to climate changes scenario, based on which feasible adaptation strategies will be adopted that are area oriented.